2001
DOI: 10.1103/physrevb.64.140503
|View full text |Cite
|
Sign up to set email alerts
|

Phonons in MgB2 by polarized Raman scattering on single crystals

Abstract: The paper presents detailed Raman scattering study of the unusually broad E2g phonon mode in MgB2 crystal. For the first time, it is shown by the polarized Raman scattering on few-micron-size crystallites with natural faces that the observed broad Raman feature really does obey the selection rules of an E2g mode. Raman spectra on high quality polycrystalline superconducting MgB2 wires reveal a very symmetric E2g phonon line near 615 cm −1 with the room temperature linewidth of 260 cm −1 only. Additional scatte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
61
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 9 publications
12
61
2
Order By: Relevance
“…The most harmonic E 2g mode in this research is located at 581 cm −1 with a broad FWHM of 285 cm −1 for the sample sintered at 850°C. The great linewidth of the E 2g mode used to be attributed to anharmonic effects in the previous literature, [10][11][12]22,24,25 which seems to contradict the trend of the frequency shift in this research. Theoretical calculations have demonstrated that the Raman data can be explained if dynamical effects beyond the adiabatic Born-Oppenheimer approximation and electron lifetime effects are included in the phonon self-energy, without invoking anharmonicity.…”
Section: Methodscontrasting
confidence: 45%
See 1 more Smart Citation
“…The most harmonic E 2g mode in this research is located at 581 cm −1 with a broad FWHM of 285 cm −1 for the sample sintered at 850°C. The great linewidth of the E 2g mode used to be attributed to anharmonic effects in the previous literature, [10][11][12]22,24,25 which seems to contradict the trend of the frequency shift in this research. Theoretical calculations have demonstrated that the Raman data can be explained if dynamical effects beyond the adiabatic Born-Oppenheimer approximation and electron lifetime effects are included in the phonon self-energy, without invoking anharmonicity.…”
Section: Methodscontrasting
confidence: 45%
“…The optical E 2g phonon has been found theoretically to lie in the frequency region 515-665 cm −1 , 8,10,11 and the broad feature observed in the Raman spectra of pure MgB 2 around 600 cm −1 ͑width ϳ300 cm −1 ͒ has been attributed to this mode. 10,[12][13][14] The significant broadening of this Raman peak arises mainly from the exceptionally strong electron-phonon coupling of the E 2g mode to the partially occupied planar boron bands near the Fermi surface, 11,15 which is due to their large anharmonicities. 11,16 Since the lattice distortion is one of the most important factors to influence the critical current density J c ͑H͒ it is expected that the changes in the Raman spectra due to the different material processing conditions may reflect changes in the superconducting properties of MgB 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the origin of the central ν 2 band is still questioned, 11,12 it is generally assigned to the Ramanactive mode E 2g , to which theoretical predictions attribute a peak frequency 6,7,9,12,17,18 ranging from 470 to 660 cm −1 . It is worth noticing that further spectral contributions observed in previous Raman experiments 10,12 have been ascribed to peaks in the phonon density of states (around 430, 620, 710 and 780 cm −1 ) derived from neutron scattering experiments. 19 In a disordered or defective system, the momentum selection rules can indeed be violated, and the Raman (or infrared absorption) spectrum can reflect the phonon density of states.…”
mentioning
confidence: 99%
“…It is quite a general statement that the E 2g mode is expected to allow for the strongest e-ph coupling [5][6][7] and then to play a relevant role in superconductivity. Raman experiments [8][9][10][11][12] carried out on MgB 2 have shown that the spectrum is dominated by a quite large and asymmetric band around 600 cm −1 , ascribed to the E 2g mode. The anomalous width of this phonon peak has been interpreted as a signature of the e-ph coupling.…”
mentioning
confidence: 99%
See 1 more Smart Citation